1994
DOI: 10.1152/ajprenal.1994.266.3.f506
|View full text |Cite
|
Sign up to set email alerts
|

Arginine vasopressin and forskolin regulate apical cell surface expression of epithelial Na+ channels in A6 cells

Abstract: Both arginine vasopressin (AVP) and forskolin regulate vectorial Na+ transport across high-resistance epithelia by increasing the Na+ conductance of the apical membrane mediated by amiloride-sensitive Na+ channels. Pretreatment of A6 cells with brefeldin A partially inhibited the increase in Na+ transport in response to forskolin, suggesting recruitment of Na+ channels from an intracellular pool. The activation of Cl- secretion was not affected. Apical cell surface expression of Na+ channels was examined follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
55
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 0 publications
9
55
0
Order By: Relevance
“…This will increase the apical Ca2+ influx and, therefore, stim ulate transcellular transport of Ca2+. A similar m echanism has been postulated for th e stim ulatory effect of PTH on Ca2+ influx in the distal nephron and for the effect of vasopressin on epithelial Na+ channels [26,29,30].…”
Section: Discussionmentioning
confidence: 67%
“…This will increase the apical Ca2+ influx and, therefore, stim ulate transcellular transport of Ca2+. A similar m echanism has been postulated for th e stim ulatory effect of PTH on Ca2+ influx in the distal nephron and for the effect of vasopressin on epithelial Na+ channels [26,29,30].…”
Section: Discussionmentioning
confidence: 67%
“…The FLAG epitope allows the number of ENaC subunits residing in the apical membrane of the transfected MDCK cells to be quantified by the surface binding of 125 I-labeled anti-FLAG antibodies. Our initial studies with intact FL-MDCK monolayers in DMEM medium showed they had a high shortcircuit current (I sc ) and that cAMP treatment produced a rapid transient peak within 5 min followed by a broad peak that decayed over 20 min (43), as also described in A6 and M-1 cultures (8,29,34,44). The biphasic response to cAMP in all of these epithelia has been attributed to rapid Cl Ϫ secretion by CFTR activation followed by a slower cAMP-dependent activation of ENaC that is blunted by the inhibitory effect of CFTR.…”
mentioning
confidence: 77%
“…However, earlier studies in A6 cells showed that aldosterone increases Na ϩ entry at the apical membrane by changing the activity of channels that are already present in the apical membrane and not by increasing the number of channels (13). Although interpretation of other electrophysiological data remains controversial (14 -16), biochemical methods support the original observation that ENaC mRNA and ENaC protein in the apical membrane does not increase in the presence of aldosterone (at least in the first 2-4 h when the increase in sodium transport is most dramatic) (10,(17)(18)(19).Since the action of aldosterone appears to involve a mechanism that increases the P o of sodium channels, an examination of post-translational mechanisms that alter P o may offer some insight into the mechanism of aldosterone action, but identifying signal transduction pathways that can increase sodium channel P o in A6 cells has been difficult. There have been many suggestions about potential aldosterone-induced post-translational modifications, but in the context of our previous results (20 -22), one is particularly interesting.…”
mentioning
confidence: 82%
“…However, earlier studies in A6 cells showed that aldosterone increases Na ϩ entry at the apical membrane by changing the activity of channels that are already present in the apical membrane and not by increasing the number of channels (13). Although interpretation of other electrophysiological data remains controversial (14 -16), biochemical methods support the original observation that ENaC mRNA and ENaC protein in the apical membrane does not increase in the presence of aldosterone (at least in the first 2-4 h when the increase in sodium transport is most dramatic) (10,(17)(18)(19).…”
mentioning
confidence: 89%